Layered double hydroxides for corrosion-related applications—Main developments from 20 years of research at CICECO - Tedim, João; Galvão, Tiago L. P.; Yasakau, Kiryl A.; Bastos, Alexandre; Gomes, José R. B.; Ferreira, Mario G. S. (Frontiers in Chemistry, 2022)
This work describes the main advances carried out in the field of corrosion protection using layered double hydroxides (LDH), both as additive/pigment-based systems in organic coatings and as conversion films/pre-treatments. In the context of the research topic “Celebrating 20 years of CICECO”, the main works reported herein are based on SECOP’s group (CICECO) main advances over the years. More specifically, this review describes structure and properties of LDH, delving into the corrosion field with description of pioneering works, use of LDH as additives to organic coatings, conversion layers, application in reinforced concrete and corrosion detection, and environmental impact of these materials. Moreover, the use of computational tools for the design of LDH materials and understanding of ion-exchange reactions is also presented. The review ends with a critical analysis of the field and future perspectives on the use of LDH for corrosion protection. From the work carried out LDH seem very tenable, versatile, and advantageous for corrosion protection applications, although several obstacles will have to be overcome before their use become commonplace.